A bibliometric study on organization citizenship behavior for the environment - M.M. Sulphey; N.S. AlKahtani; N.A.M. Senan; A.H.E. Adow (Global Journal of Environmental Science and Management)
Organization Citizenship Behavior for the Environment is discretionary and proactive behavior that contributes to more effective environmental management by organizations. It originates from the organizational behavior concepts of organizational citizenship behavior and discretionary pro-environmental behaviors. As environmental challenges have become more complex, they cannot be managed solely through formal procedures. Thus, there is a need for Organization Citizenship Behavior for Environment. It does not prescribe the pro-environmental behaviors employees are expected to engage in. Organization citizenship behaviour for the environment includes various workplace environment management initiatives, such as sharing knowledge that can prevent pollution, providing solutions for waste reduction, and implementing environmentally friendly technologies. This study aimed to synthesize the literature on Organization Citizenship Behaviour for the environment through a bibliometric analysis. Bibliometrics is a methodology that analyzes academic research and addresses massive volumes of information. It is a big data analytics technique used in systematic literature reviews and entails quantitatively analyzing scholarly works. It examines research trends, productivity, and scientifically linked patterns in-depth. Journal publications from 2000 were downloaded from the Scopus repository in comma-separated values and plain-text formats. The VOSviewer program was used to visualize and analyze various trends and patterns in the available literature. The results show that the literature on Organization Citizenship Behavior for the environment is increasing rapidly, as are the citations of the topic. Over the past decade, 187 articles have been published on this topic. In the same period, the term organization citizenship behavior for the environment was found to be a keyword used 54 times. This trend is expected to continue. This study contributes to an improved understanding of the emerging concept of organization citizenship behaviour in the environment. This study presented a macroscopic summary of the main characteristics of organization citizenship behaviour in the environment, which was not attempted earlier. This study also discusses the limitations and scope for future research. These limitations include limiting the study to the Scopus database and methodology used. For instance, the bibliometric method is sensitive to the selection criteria and filters used to construct a sample. It is possible that the selection criteria concealed certain relevant articles based on the search query used in the study.